Kajian Desain Fender Di Pelabuhan Benoa Bali Sesuai British Standart 6349-2014 - Budiono Joko Nugroho; Istirokhatun, Titik; Sumardi (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
Fenders in dock buildings are damage prevention when ships dock at the dock. The fender design must be appropriate so that it can absorb impact energy. The amount of energy absorbed and the maximum force transmitted to the dock structure are used to determine the type and size of the fender. At Benoa Pier Bali where long cruise ships are anchored, a larger fender design is required. There are various methods for determining fender design, one of which uses British Standard 6349-2014 part 4: Code of practice for design of fendering and mooring systems. PT. Pelabuhan Indonesia as a port operator in Indonesia has historically used various fender design methods. The use of British Standard 6349 - 2014 has various advantages in designing a fender, where various factors influence the selection of fenders such as wave conditions, currents, wind, ship size, speed and direction of the ship when anchored at the dock. The SSCnF Cone 1100 + Frontal Frame fender is used according to the calculation results using BS 6349 - 2014.